Factor Affecting Treatment Compliance in TB Patients - Vita Lucya; Nabila Triefitriani Arief (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Pulmonary Tuberculosis is a disease caused by  Mycobacterium tuberculosis that invades the lungs. Indonesia ranks second as the country with the highest number of pulmonary TB in the world.  The treatment coverage of Pulmonary TB in Indonesia in 2022 is only 25% of the target (80%). One of the risk factors that cause treatment failure is medication adherence. Objective:  This study aims to determine the factors that influence medication adherence in patients with pulmonary TB.  Methods:  This study used a quantitative descriptive design with a cross-sectional study on 33 patients with pulmonary TB who became respondents by using total sampling. This study uses more than one instrument including Morisky Medication Adherence Scale-8, Generic Assessment of Side Effects, Multidimensional Scale of Perceived Social Support. The  data analysis that  were used in this study are Pearson Product Moment, Chi-square, Kruskal-wallis, and Simple Linear Regression. Results:  The results of this study on factors related to medication adherence on TB patients showed that age, level of education, duration of treatment, drug side effects, and family support were related to medication adherence of pulmonary TB patients. alone. Conclusion: This study showed that to achieve medication adherence requires the continuity of various factors and does not depend on one factor Future researchers  are expected to examine other factors that can affect medication adherence in patients with Pulmonary TB.